(untitled) (National Administration Journal, 2014)
This paper introduces a model for the demand of books and other periodic publications (BPP) in Spain based on micro-data from household budget surveys corresponding to 2006, 2007, and 2008. The model is formulated with a truncated or censored dependent variable in which selection is made using a probit model that determines the possibility of whether a given item is purchased or not. Then, based on the results from the initial model, the factors that determine expenditure on BPP are identified. Alternatively, a tobit model has been used. The paper is mainly focused on identifying the price and income elasticity of demand, as well as the influence of various demographic factors such as sex and age, both on the probability of purchase as well as on the expenditure made on BPP.